Pengetahuan dan sikap terhadap perilaku penggunaan masker dalam pencegahan penularan Covid-19 pada mahasiswa - Juwi Athia Rahmini (Holistik Jurnal Kesehatan, 2023)
Background: The history of cases of transmission of covid-19 in Indonesia is very high, especially in the city of Medan. Observations made show that students still do not follow the attitude of using the mandatory three-layer mask or disposable masks when adjusting to face-to-face learning is limited. The attitude of the students looks normal and they are not worried about contracting a covid-19 infection or the omicron variant. The results of interviews with students stated that in the surrounding environment, the use of masks was rare, even from information obtained online that the use of masks did not necessarily prevent the transmission of infections from various diseases. Furthermore, the ease of access to obtaining knowledge about the use of masks in preventing transmission of covid-19 in the 4.0 era can influence student attitudes. Even though the omicron variant has appeared as many as 414 positive confirmed cases in Indonesia. No similar research has been conducted at the Binalita Sudama High School in Medan.Purpose: Identify the relationship between the level of knowledge and attitudes against face mask-wearing behaviors to prevent Covid-19 among studentsMethod: A quantitative study using a correlation descriptive research design, with a total sampling technique with a non-random sampling method. The sample size was all students as 100 respondents. Questionnaires were used to obtain demographic data, attitudes, and the level of student's knowledge of the behavior of wearing masks.Results: Shows a high level of student knowledge and positive attitudes about the use of masks. The results of the analysis show that there is no relationship between the level of knowledge and attitudes toward the behavior of wearing masks.Conclusion: The student's knowledge and attitudes toward the behavior of wearing masks, which can be used as a basis for further qualitative research.Keywords: Knowledge; Attitudes; Behaviors; Mask; Prevention;  Covid-19; StudentsPendahuluan: Riwayat kasus penularan covid-19 di Indonesia sangat  tinggi, khususnya kota Medan. Observasi yang dilakukan menunjukkan mahasiswa masih belum  mengikuti sikap penggunaan wajib masker tiga lapis atau masker  sekali pakai saat  penyesuain pembelajaran tatap muka terbatas. Sikap mahasiswa  terlihat  biasa saja dan tidak khawatir  tertular  infeksi covid-19 atau varian omicron.  Hasil wawancara kepada mahasiswa menyatakan dilingkungan sekitarnya penggunaan masker sudah jarang, bahkan dari informasi yang didapat secara online bahwa penggunaan masker belum tentu dapat mencegah penularan infeksi dari berbagai penyakit. Selanjutnya,  kemudahan akses mendapatkan informasi pengetahuan tentang penggunaan masker dalam mencegah penularan covid-19 di era 4.0 dapat mempengaruhi sikap mahasiswa. Padahal varian omicron telah muncul sebanyak 414 kasus terkonfirmasi positif di Indonesia. Penelitian yang serupa belum ada dilakukan di Sekolah Tinggi Binalita Sudama Medan.Tujuan: Mengidentifikasi hubungan tingkat pengetahuan dan sikap terhadap perilaku penggunaan masker dalam pencegahan penularan Covid-19 pada mahasiswaMetode: Penelitian kuantitatif dengan menggunakan design penelitian deskriptif korelasi, dengan teknik total sampling dengan metode non-random sampling dan seluruh mahasiswa STIKes Binalita angkatan tahun 2019 sebagai 100 responden. Kuesioner digunakan untuk memperoleh data demografi, sikap dan tingkat pengetahuan mahasiswa terhadap perilaku penggunaan masker.Hasil: Menunjukkan tingkat pengetahuan mahasiswa tinggi dan sikap positif tentang penggunaan masker. Hasil analisa menunjukkan tidak terdapat hubungan antara tingkat pengetahuan dan sikap terhadap perilaku penggunaan masker.Simpulan: Menjadi gambaran pengetahuan dan sikap mahasiswa terhadap perilaku penggunaan masker, yang dapat dijadikan landasan dilakukan penelitian lanjutan secara kualitatif.